A ERA DIGITAL: A QUESTÃO DA LIBERDADE DE EXPRESSÃO E DO DIREITO DE INFORMAÇÃO NA REDE MUNDIAL - Amaral, Sérgio Tibiriçá; Yabunaka, Fabricio Miguel (Revista da AJURIS, 2022)
THE DIGITAL PERIOD: THE QUESTION OF FREEDOM OF EXPRESSION AND RIGHT OF ACESS TO INFORMATION IN THE WORLDWIDE NETWORK ÁREA(S): direito constitucional. RESUMO: O presente trabalho visou a abordar a liberdade de expressão relacionada com o direito de resposta e o direito de informação. Tratou-se da terceira dimensão de direitos fundamentais com ênfase na Declaração Universal de Direitos do Homem da Organização das Nações Unidas de 1948 – além da liberdade de expressão no Brasil em todas as Constituições. Foi a Constituição Federal de 1988 que falou da livre manifestação do pensamento na forma de dez direitos, mas apenas três deles foram abordados neste trabalho. Fez-se necessário destacar que a liberdade de expressão e o direito de informação possuem limitadores como os direitos da personalidade e o direito de resposta, sendo discutida a ponderação entre esses direitos. Por fim, foi realizada uma distinção entre a liberdade de expressão e o direito de informação. Para a pesquisa, além da bibliográfica, foram utilizados o método dedutivo, o método indutivo e o método histórico. ABSTRACT: The present work aims to address the freedom of expression related to the Right of reply and the right of access to information. Besides, it became essential to mention the third dimension of fundamental Rights and also the Universal Declaration of Human Rights (UDHR) by United Nations, 1948. It has been the Freedom of expression in Brazil. Went the Federal Constitution of 1988 talks about of Free Freedom of Thought in form of ten rights, but only three rights were mentioned in this work: It was necessary to emphasize the freedom of expression and right of access to information are both limiting and none of them has a limited right, So it’s possible to limit: Right relating to personality and The Right of Reply, It was discussed the importance between the right of access to information and right relating to personality. Finally, It was established a difference between Freedom and the right of access to information. The bibliographic search, the deductive and inductive reasoning, and also historical method were the methods for this search. PALAVRAS-CHAVE: liberdade; pensamento; informação; Constituição; direitos fundamentais. KEYWORDS: freedom; thought; information; Constitution; fundamental rights. SUMÁRIO: Introdução; 1 Direitos relativos à manifestação do pensamento na rede mundial; 2 Terceira dimensão de direitos fundamentais; 3 Liberdade de expressão; 4 Direito de antena ou positivo e a internet; 5 Direito de se informar; 6 Direito de ser informado; 7 Limites do direito de informação na rede; Conclusão; Referências. SUMMARY: Introduction; 1 Rights relating to manifestation of thought in worldwide network; 2 Third dimension of fundamental Rights; 3 Freedom of expression; 4 Antenna Right or positive and internet; 5 Right of inform your self; 6 Right to be informed; 7 Limits of right of information on the network; Conclusion; References.